New species and records of Anthelephila praetor species-group (Coleoptera: Anthicidae) from China - Zhao, Yuchen; Wang, Xinpu (Zootaxa, 2024)
Three new species of the genus Anthelephila Hope, 1833 are described: A. androgyna n. sp. (Hainan), A. junpolis n. sp. (Hainan) and A. tricolorata n. sp. (Yunnan). New distributional records of A. celer (Kejval, 1999) from Yunnan are added, known records distribution map of A. praetor informal species-group is provided.